Preparation method of low-loss iron-silicon-titanium soft magnetic powder core

By performing air atmosphere heat treatment and nano-oxide insulation coating on the ferrosilicon titanium soft magnetic powder core, and high-temperature heat treatment under the protection of inert gas, the problem of high loss of powder core is solved, and the improvement of low loss and high magnetoelectric performance is achieved. .

CN119419057APending Publication Date: 2025-02-11YANGZHOU LEADING INNOVATION MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411819046.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The internal stress introduced by the existing ferrosilicon titanium soft magnetic powder core during the pressing process leads to high losses, and increasing the heat treatment temperature will destroy the organic insulation coating layer and affect the performance of the powder core.

Method used

The air atmosphere heat treatment is carried out using ferrosilicon titanium metal soft magnetic powder, followed by insulating coating with phosphoric acid, nano-oxide and water, and high-temperature heat treatment is carried out under the protection of inert gas, and finally sprayed with epoxy resin coating to enhance the powder core. performance.

Benefits of technology

It effectively reduces the hysteresis loss of the iron-silicon titanium powder core and improves its comprehensive magnetoelectric performance, especially the volume loss under 50kHz and 100mT conditions is less than 200mW/cm3.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419057A_ABST
    Figure CN119419057A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a low-loss iron-silicon-titanium soft magnetic powder core, which comprises the following steps of: carrying out heat treatment on iron-silicon-titanium magnetic powder in an air atmosphere, and carrying out surface secondary passivation, insulating coating and blocking of an eddy current loop among magnetic powder particles through a phosphoric acid solution and a nano oxide to prepare the low-loss 60-mu iron-silicon-titanium powder core. The 60mu Fe-Si-Ti soft magnetic powder core has excellent magnetoelectric performance, and under the conditions of 50kHz and 100mT, the volume loss of the 60mu Fe-Si-Ti soft magnetic powder core is lower than 200mW / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a method for preparing a low-loss iron silicon titanium soft magnetic powder core. Background Art

[0002] As power electronic devices are rapidly developing towards high frequency, high power and miniaturization, the application market of metal soft magnetic powder cores has been further expanded, and higher requirements have been put forward for the comprehensive magnetic and electrical properties of metal soft magnetics. Common metal soft magnetic powder cores include iron silicon aluminum, iron silicon, iron nickel, iron nickel molybdenum, etc., which are mainly used in various filters, power inductors, inverters and other devices.

[0003] Metal titanium has excellent properties such as high strength, low density, excellent corrosion resistance, good heat resistance and low temperature resistance. The introduction of Ti element into FeSi alloy can reduce the magnetocrystalline anisotropy constant and magnetostriction coefficient of FeSi alloy, increase the resistivity of the material, and thus improve the soft magnetic properties of the alloy. Patent CN108565108B discloses an iron silicon titanium magnetic powder core and a preparation method thereof. After mixing iron silicon titanium alloy powder and silicone resin solution, the resin mixture is dried to obtain a resin mixture; the resin mixture is pressed and annealed in sequence to obtain an iron silicon titanium magnetic powder core. The volume loss under 50kHz and 50mT conditions is 118.94~204.32mW / cm 3 , the magnetic permeability is 38.8~61.6. Since the patent uses organic matter to insulate the surface of iron-silicon-titanium soft magnetic powder, a lower annealing temperature of 200~500°C is used, which cannot effectively eliminate the internal stress introduced by the powder core during the pressing process, resulting in high losses. If the heat treatment temperature is increased, the organic insulating coating layer is easily damaged, which will cause the powder core loss performance to deteriorate. Patent CN116809955A discloses a method for preparing a corrosion-resistant high-entropy alloy coating containing cobalt, chromium, iron, nickel and titanium. The alloy powder containing cobalt, chromium, iron, nickel and titanium elements is used as an additive, and a corrosion-resistant high-entropy alloy coating is printed on the surface of the metal matrix material through 3D printing. It has no pores, no impurities, no cracks and excellent corrosion resistance.

[0004] Through the analysis of the existing technology, it can be seen that by introducing the Ti element, the performance stability of the FeSi series material can be effectively improved, especially the corrosion resistance of the material can be improved. The present invention uses iron silicon titanium metal soft magnetic powder as the material base material for preparing the powder core, uses a secondary passivation method to perform surface treatment on the magnetic powder, and uses nano-oxide to perform insulation coating treatment on the magnetic powder, which can greatly reduce the loss of the iron silicon titanium powder core and improve the comprehensive magnetic and electrical properties of the powder core. Summary of the invention

[0005] In response to the demand for improving the performance of soft magnetic powder cores in the field of electronic power devices, the present invention provides a method for preparing a low-loss FeSiTi soft magnetic powder core, which can greatly reduce the volume loss of the FeSiTi powder core and improve the comprehensive magnetoelectric performance.

[0006] The method for preparing the low-loss iron silicon titanium soft magnetic powder core of the present invention comprises the following steps:

[0007] Step 1: heat treating the iron silicon titanium soft magnetic powder in an air atmosphere;

[0008] Step 2: uniformly mix the obtained pretreated powder with phosphoric acid, nano oxide and water, heat and stir while keeping warm; after the insulation is completed, naturally cool to room temperature, and sieve to obtain a dry powder;

[0009] Step 3: Sieve the dry powder obtained in step 2 through a 100-mesh sieve, then add a release agent, mix well, and obtain magnetic powder to be formed;

[0010] Step 4: Using a press machine, press the magnetic powder to be formed prepared in step 3 into a powder core blank;

[0011] Step 5: Under the protection of inert gas, the powder core blank pressed in step 4 is kept at 700° C. to 770° C. to obtain a semi-finished magnetic powder core;

[0012] Step 6: Spray a layer of insulating, high temperature resistant epoxy resin coating onto the surface of the semi-finished magnetic powder core obtained in step 5 to obtain a finished metal soft magnetic powder core.

[0013] In step 1, the original powder particle size of the iron silicon titanium soft magnetic powder is ≤200 mesh, and its composition by mass percentage is: Si 4.5% to 6.5%, Ti 0.5% to 2.0%, and the balance is Fe.

[0014] In step 1, the air atmosphere heat treatment temperature is 300° C. to 400° C., and the heat preservation time is 30 minutes to 60 minutes.

[0015] In step 2, the selected phosphoric acid concentration is 85%, the added mass of phosphoric acid is 0.5% to 2.5% of the mass of the iron silicon titanium soft magnetic powder, the added mass of water is 18.0% to 28.0% of the mass of the iron silicon titanium soft magnetic powder, and the added mass of nano-oxide is 0.5% to 1.5% of the mass of the iron silicon titanium soft magnetic powder.

[0016] Furthermore, the nano-oxide is one or a mixture of silicon oxide, aluminum oxide, kaolin, magnesium oxide, etc.

[0017] In step 2, the mixed slurry is heated to a temperature of 80° C. to 100° C., and the insulation time is 40 minutes to 90 minutes.

[0018] In step 4, the pressing pressure is 1700MPa to 2000MPa.

[0019] In step 5, the inert protective gas is one of nitrogen and hydrogen, or a mixed gas.

[0020] In step 5, the insulation time is 100 minutes to 150 minutes.

[0021] The effective magnetic permeability of the low-loss iron silicon titanium soft magnetic powder core prepared by the present invention is 60μ, and the volume loss Pcv under the conditions of 50kHz and 100mT is less than 200mW / cm 3 .

[0022] The present invention uses iron silicon titanium metal soft magnetic powder as the material system for preparing soft magnetic powder core, which has higher corrosion resistance and can improve the performance stability of the powder core. First, the iron silicon titanium powder is pretreated in an air atmosphere, and the powder surface can be evenly oxidized and insulated. Then, the magnetic powder is insulated and coated with nano-oxide, which can further improve the thermal stability of the insulation layer of the powder core, thereby increasing the subsequent heat treatment temperature of the powder core, effectively removing the internal stress of the powder core, greatly reducing the hysteresis loss of the powder core, and improving the comprehensive magnetoelectric properties of the powder core. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The relationship between the inductance L and the quality factor Q of the iron silicon titanium powder core provided in Example 1 of the present invention and the frequency f.

[0024] Figure 2 The DC bias performance of the iron silicon titanium powder core provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the examples. The described examples and their results are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0026] Embodiment 1:

[0027] 1000.0 g of 200-mesh iron silicon titanium magnetic powder was selected and heat-treated in an air atmosphere at 300° C. for 60 minutes to obtain a pretreated powder; the pretreated powder was uniformly mixed with 5.0 g of phosphoric acid, 280.0 g of water and 15.0 g of silicon oxide, heated to 80° C., and kept at 80° C. for 90 minutes to obtain an insulation-coated powder; the insulation-coated powder was sieved with a 100-mesh sieve, and then 3.0 g of a release agent was added to the powder, and after mixing evenly, a finished product was obtained. The method comprises the following steps: preparing a powder by forming a powder; pressing the uniformly mixed magnetic powder to be formed into a powder core blank at a pressing pressure of 2000 MPa, wherein the powder core blank is a ring-shaped powder core with an outer diameter of 27.00 mm, an inner diameter of 14.80 mm, and a height of 11.18 mm; using nitrogen as a protective gas, the pressed powder core blank is kept at 770°C for 100 minutes to obtain a semi-finished magnetic powder core; finally, spraying a layer of insulating and high-temperature resistant epoxy resin coating on the surface of the semi-finished magnetic powder, and drying to obtain a finished metal soft magnetic powder core.

[0028] Embodiment 2:

[0029] 1000.0 g of 200-mesh iron silicon titanium magnetic powder was selected and heat-treated in an air atmosphere at 320° C. for 50 minutes to obtain a pretreated powder; the pretreated powder was uniformly mixed with 8.0 g of phosphoric acid, 260.0 g of water and 12.0 g of aluminum oxide, heated to 85° C., and kept at 85° C. for 80 minutes to obtain an insulation-coated powder; the insulation-coated powder was sieved with a 100-mesh sieve, and then 3.0 g of a release agent was added to the powder, and after mixing evenly, a finished product was obtained. The method comprises the following steps: preparing a powder core blank by pressing the uniformly mixed magnetic powder to be formed into a powder core blank at a pressing pressure of 1900 MPa, wherein the powder core blank is a ring-shaped powder core with an outer diameter of 27.00 mm, an inner diameter of 14.80 mm, and a height of 11.18 mm; using hydrogen as a protective gas, the pressed powder core blank is kept at 760° C. for 110 minutes to obtain a semi-finished magnetic powder core; finally, spraying a layer of insulating and high-temperature resistant epoxy resin coating on the surface of the semi-finished magnetic powder, and drying to obtain a finished metal soft magnetic powder core.

[0030] Embodiment 3:

[0031] 1000.0 g of 200-mesh iron silicon titanium magnetic powder was selected and heat-treated in an air atmosphere at 345° C. for 45 minutes to obtain a pretreated powder; the pretreated powder was uniformly mixed with 12.0 g of phosphoric acid, 220.0 g of water and 9.3 g of magnesium oxide, heated to 90° C., and kept at 90° C. for 60 minutes to obtain an insulation-coated powder; the insulation-coated powder was sieved with a 100-mesh sieve, and then 3.0 g of a release agent was added to the powder, and after mixing evenly, a finished product was obtained. The method comprises the following steps: preparing a powder by pressing the uniformly mixed magnetic powder to be formed into a powder core blank at a pressing pressure of 1800 MPa, wherein the powder core blank is a ring-shaped powder core with an outer diameter of 27.00 mm, an inner diameter of 14.80 mm, and a height of 11.18 mm; using nitrogen as a protective gas, the pressed powder core blank is kept at 750°C for 115 minutes to obtain a semi-finished magnetic powder core; finally, spraying a layer of insulating and high-temperature resistant epoxy resin coating on the surface of the semi-finished magnetic powder, and drying to obtain a finished metal soft magnetic powder core.

[0032] Embodiment 4:

[0033] 1000.0 g of 200-mesh iron silicon titanium magnetic powder was selected and heat-treated in an air atmosphere at 360° C. for 40 minutes to obtain a pretreated powder; the pretreated powder was uniformly mixed with 18.0 g of phosphoric acid, 200.0 g of water and 7.5 g of kaolin, heated to 100° C., and kept at 100° C. for 40 minutes to obtain an insulation-coated powder; the insulation-coated powder was sieved with a 100-mesh sieve, and then 3.0 g of a release agent was added to the powder, and after mixing evenly, a powder to be coated was obtained. molding powder; using a pressing pressure of 1700MPa to press the uniformly mixed magnetic powder to be formed into a powder core blank, wherein the powder core blank is a ring-shaped powder core with an outer diameter of 27.00mm×inner diameter of 14.80mm×height of 11.18mm; using nitrogen as a protective gas, the pressed powder core blank is kept at 720℃ for 135 minutes to obtain a semi-finished magnetic powder core; finally, spraying a layer of insulating, high-temperature resistant epoxy resin coating on the surface of the semi-finished magnetic powder, and drying to obtain a finished metal soft magnetic powder core.

[0034] Embodiment 5:

[0035] 1000.0 g of 200-mesh iron silicon titanium magnetic powder was selected and heat-treated in an air atmosphere at 400° C. for 30 minutes to obtain a pretreated powder; the pretreated powder was uniformly mixed with 25.0 g of phosphoric acid, 180.0 g of water and 5.0 g of kaolin, heated to 95° C., and kept at 95° C. for 50 minutes to obtain an insulation-coated powder; the insulation-coated powder was sieved with a 100-mesh sieve, and then 3.0 g of a release agent was added to the powder, and after mixing evenly, a powder to be molded was obtained. Finally; using a pressing pressure of 1850MPa to press the uniformly mixed magnetic powder to be formed into a powder core blank, wherein the powder core blank is a ring-shaped powder core with an outer diameter of 27.00mm×an inner diameter of 14.80mm×a height of 11.18mm; using a nitrogen-hydrogen mixed gas as a protective gas, the pressed powder core blank is kept at 700°C for 150 minutes to obtain a semi-finished magnetic powder core; finally, spraying a layer of insulating, high-temperature resistant epoxy resin coating on the surface of the semi-finished magnetic powder, and drying to obtain a finished metal soft magnetic powder core.

[0036] The magnetic and electrical properties of the iron silicon titanium soft magnetic powder core in the above embodiment are shown in the following table, wherein the wire diameter of the winding enameled wire is Φ1.00 mm, the wire length is 0.9 m, and the number of turns is 25 turns.

[0037]

[0038] It can be seen from the table that by adjusting the air atmosphere heat treatment parameters, the amount of insulating coating reagents, the pressing molding pressure and the heat treatment parameters, a 60μ iron silicon titanium powder core can be prepared, where the standard inductance corresponding to 60μ is 46.88μH, the actual controlled inductance error is -8% to 8%, and the corresponding inductance level is -8 to +8.

[0039] On the basis of FeSi alloy, the introduction of Ti element can reduce the magnetocrystalline anisotropy constant and magnetostriction coefficient and improve the soft magnetic properties of the alloy. Considering that the Ti element can improve the corrosion resistance of the material, in order to effectively modify the surface of the metal magnetic powder, a technical solution of heat treating the powder in an air atmosphere is adopted to achieve a primary passivation of the powder surface. It can be seen from the test data of the prepared powder core inductor that the technical solution disclosed in this patent can effectively adjust the iron silicon titanium powder core inductor. In addition, by adopting the coating solution of nano-oxide, the heat treatment temperature of iron silicon titanium can be increased to 700℃~770℃.

[0040] Compared with the conventional iron silicon powder core, it can be seen that under the condition of 100Oe, the DC bias performance of the iron silicon titanium powder core prepared by this scheme is not less than 77%, which is higher than 76% of the iron silicon powder core. By comparing the loss test data, it can be found that the loss of the iron silicon titanium powder core is significantly lower than the loss of the iron silicon powder core. On the one hand, due to the introduction of the Ti element, the intrinsic magnetic parameters of the powder material can be significantly improved, and the resistivity of the material body can be increased; on the other hand, the use of secondary passivation and nano-oxide insulation coating schemes can effectively block the eddy current circuits between the powder particles, reducing the eddy current loss; and by increasing the heat treatment temperature, the internal stress of the powder core can be effectively removed, thereby further reducing the hysteresis loss of the powder core. Under the test conditions of 50kHz and 100mT, the loss of the iron silicon titanium powder core prepared by the technical solution of the present invention is not higher than 200mW / cm 3 .

[0041] Figure 1 and Figure 2 They are respectively the relationship between the inductance L and the quality factor Q of the iron silicon titanium powder core provided in Example 1 of the present invention and the frequency f, and the direct current bias performance diagram of the iron silicon titanium powder core. Figure 1 It can be seen that with the increase of the test frequency, the prepared FeSiTi powder core inductance changes smoothly and has good frequency stability. The powder core quality factor Q also gradually becomes flatter with the increase of the test frequency. Figure 2 In the test, as the external test field strength increases, the inductance of the powder core gradually decays slowly. Under 200Oe conditions, the inductance decays to 44.47% of the inductance without external field strength, which is better than the 42% of the conventional iron silicon powder core. Therefore, compared with the performance of the iron silicon powder core, it can be found that the iron silicon titanium powder core has good comprehensive magnetic and electrical properties, especially excellent low loss characteristics, which can well meet the needs of the development of future power electronic devices.

Claims

1. A method for preparing a low-loss iron silicon titanium soft magnetic powder core, characterized in that: Using iron silicon titanium soft magnetic powder as raw material, it is pre-heat-treated in an air atmosphere to passivate the powder surface; then the surface is secondary passivated and insulated by phosphoric acid solution and nano-oxide to obtain a finished metal soft magnetic powder core, which greatly reduces the volume loss of the iron silicon titanium powder core.

2. The preparation method according to claim 1, characterized in that The steps include: Step 1: heat treating the iron silicon titanium soft magnetic powder in an air atmosphere; Step 2: uniformly mix the obtained pretreated powder with phosphoric acid, nano oxide and water, heat and stir while keeping warm; after the insulation is completed, naturally cool to room temperature, and sieve to obtain a dry powder; Step 3: Sieve the dry powder obtained in step 2 with a 100-mesh sieve, then add a release agent, mix well, and obtain magnetic powder to be formed; Step 4: Using a press machine, press the magnetic powder to be formed prepared in step 3 into a powder core blank; Step 5: Under the protection of inert gas, the powder core blank pressed in step 4 is kept at 700° C. to 770° C. to obtain a semi-finished magnetic powder core; Step 6: Spray a layer of insulating, high temperature resistant epoxy resin coating onto the surface of the semi-finished magnetic powder core obtained in step 5 to obtain a finished metal soft magnetic powder core.

3. The preparation method according to claim 2, characterized in that: In step 1, the original powder particle size of the iron silicon titanium soft magnetic powder is ≤200 mesh, and its composition by mass percentage is: Si 4.5% to 6.5%, Ti 0.5% to 2.0%, and the balance is Fe.

4. The preparation method according to claim 2, characterized in that: In step 1, the air atmosphere heat treatment temperature is 300° C. to 400° C., and the heat preservation time is 30 minutes to 60 minutes.

5. The preparation method according to claim 2, characterized in that: In step 2, the selected phosphoric acid concentration is 85%, the added mass of phosphoric acid is 0.5% to 2.5% of the mass of the iron silicon titanium soft magnetic powder, the added mass of water is 18.0% to 28.0% of the mass of the iron silicon titanium soft magnetic powder, and the added mass of nano-oxide is 0.5% to 1.5% of the mass of the iron silicon titanium soft magnetic powder.

6. The preparation method according to claim 5, characterized in that: The nano oxide is one or a mixture of silicon oxide, aluminum oxide, kaolin, magnesium oxide and the like.

7. The preparation method according to claim 2, characterized in that: In step 4, the pressing pressure is 1700MPa to 2000MPa.

8. The preparation method according to claim 2, characterized in that: In step 5, the insulation time is 100 minutes to 150 minutes.

Citation Information

Patent Citations

  • A Ferrosilicon-Titanium Magnetic Powder Core, Its Preparation Method and Application

    CN108565108B

  • Preparation method of corrosion-resistant high-entropy alloy coating containing cobalt, chromium, iron, nickel and titanium

    CN116809955A